Penggunaan Business Model Canvas sebagai Upaya Menumbuhkan Minat Berwirausaha - Fiqih Hidayah (Jurnal Al-Tatwir, 2021)
Indonesian's people interest in entrepreneurship is still relatively low compared to other countries. This is due to the various perceptions that people have before starting a business. Entrepreneurship nowadays is no longer just about talent, but it can also be trained and learned. When starting a business, it is crucial to have a strategy to start a business. In order to have a structured business, understanding the kinds of business model to use can help design the most important aspects of the business. The current research aims to describe the use of Canvas business model as a tool in developing business models and determining the value given to customers and the value of the obtained benefits in a simple way so that it fosters interest in entrepreneurship. One of the factors that can help interest in entrepreneurship grow is having knowledge about entrepreneurship. Several relevant studies show that there are benefits from using the Canvas business model, namely making clear, simple, and non-financially capable plans that will provide time effectiveness and will be more financially efficient in terms of operating costs.